Evaluation of female overactive bladder using urodynamics: relationship with female voiding dysfunction - Cho,Kang Jun (2015)
ABSTRACTPurpose:To investigate the role of urodynamic study (UDS) in female patients with overactive bladder (OAB) analyzing the relationship between OAB symptoms and female voiding dysfunction (FVD).Materials and Methods:We analyzed the clinical and urodynamic data of 163 women with OAB symptoms. OAB symptoms were categorized as dry and wet. FVD was described as detrusor underactivity (DUA), which was defined as a maximum flow rate (Qmax) of ≤15mL/s associated with a detrusor pressure at Qmax (PdetQmax) of ≤20cmH2O, along with bladder outlet obstruction (BOO), which was defined as a Qmax of ≤15mL/s with a PdetQmax of >20cmH2O. Clinical and urodynamic results were compared between patients with dry and wet symptoms and between those with and without FVD.Results:78 (47.9%) had dry, and 85 (52.1%) had wet symptoms. The entire group had a relatively low Qmax (15.1±6.6mL/s) and relatively high number of BOO (42.9%, 70/163) and DUA (8.6%, 14/163). A significantly higher number of patients with wet symptoms had detrusor overactivity compared to those with dry, as detected by the UDS (p<0.05). No significant differences were found in BOO and DUA number between dry and wet groups. Further, the international prostate symptom score did not different significantly between patients with and without FVD.Conclusion:A significant number of women with OAB had voiding dysfunction. However, the OAB symptoms themselves were not useful for predicting the presence of FVD. Therefore, UDS may be necessary for accurate diagnosis in women with OAB symptoms.